Effectiveness of Local Wisdom-Based Project-Based Ethnopedagogical Learning in Enhancing Students’ Critical Literacy: A Quasi-Experimental Study - Saidil Mursali; Septiana Dwi Utami; Sri Nopita Primawati; Ika Nurani Dewi; Akhmad Sukri (Faculty of Tarbiyah and Teacher Training UIN Jurai Siwo, Lampung, 2026)
This study aims to analyze the effectiveness of Project-Based Ethnopedagogical Learning (PBEL) based on local wisdom in enhancing students’ critical literacy. Local wisdom, which has long been part of the community’s cultural identity, is viewed as having the potential to serve as a contextual learning resource capable of stimulating higher-order thinking skills. The study used a quasi-experimental non-equivalent control group design involving 69 Grade X students from two intact classes selected through purposive sampling at SMA Negeri 4 Mataram, Indonesia. Class X-6 (35 students) received PBEL based on Lombok local wisdom, while Class X-7 (34 students) followed conventional learning. The PBEL intervention integrated project activities with the exploration and revitalization of local wisdom values through culturally contextual learning tasks. The critical literacy instrument was developed based on the indicators of interpretation skills, analysis skills, inference skills, evaluation skills, and self-regulation skills. Data were analyzed using ANCOVA and Least Significant Difference (LSD) tests to examine the effectiveness of the treatment. The results showed a significant class effect on posttest critical literacy after controlling for pretest scores, F = 93.010, Sig. = 0.000, partial η² = 0.585, with a higher adjusted mean in the PBEL class (86.78) than in the conventional class (65.36). These findings indicate that PBEL offers practical novelty by transforming local wisdom into project-based inquiry and reflection activities that strengthen both cultural identity and critical literacy. This study implies that local wisdom-based PBEL can be adopted as a contextual instructional strategy for critical literacy development in Indonesian secondary education.